The role of tax accounting as a tool in light of the problematic shadow economy in the Kingdom of Saudi Arabia - Azza Helmy Mahmoud Shalaby (Accounting, 2022)
The increasing phenomenon of the shadow economy is progressing dramatically in the absence of State culture among officials, whether legislators or implementers, in the absence or ineffectiveness of an organized production sector. Non-compliance with tax accounting procedures is one of the first problems generated by the shadow economy and most difficult not to include it in national output. The lack of tax commitment in the shadow economy leads to an annual tax gap of billions of dollars, if there is no logical interest on the part of the taxing bodies in developing countries, and if domestic and international tax provisions and legislation are not amended to consider of these important economic developments, and how to keep up with this. The issue of the shadow economy is thorny, and the practical way to raise the revenue needed to finance government spending on the goods and services required by society lies in the local and international tax treatment at the technical and legislative levels. Consequently, the current tax systems and their related regulations must be prepared, whether at the technical or legislative level, especially in light of the flow rate of oil barrels and the alternative if it comes into force. The taxation processes allow time to study the tax accounting and tax and take what suits the Saudi environment from them - lessons for the Kingdom of Saudi Arabia, Critical terms for research/shadow economy, tax regulations and systems, tax gab, tax accounting.